FACTORS INFLUENCING TAX COMPLIANCE IN THE TECHNICAL IMPLEMENTATION UNIT OF KUPANG REGENCY REGIONAL REVENUE AGENCY - Manafe, David; Tisu, Rosadalima; Kase, Ewaldus (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2023)
Taxes as one of the sources of state income are used for infrastructure development and other needs. With good control over tax collection, it will avoid extortion and other fraudulent practices and follow the applicable rules. The Unit of the Kupang Regency Regional Revenue Agency, there is a problem with surface water tax revenues that fluctuate and tend to increase so that they are not in line with the target. The purpose of this research is used to explain Service Quality, Tax Knowledge, and Tax Audit on Taxpayer Compliance and its effect on Surface Water Tax Revenue. The research used quantitative methods in 22 PDAM and Non-PDAM companies at the Kupang Regency Regional Revenue Agency. The population and samples in this research are 62 people. The analysis technique used in this research is SEM (Structural Equation Model). Data collection in this research by distributing questionnaires given to respondents and designed to produce specific information. The results of the questionnaire were then analyzed using the SmartPLS analysis tool. The direct test results show that service quality has a significant effect on taxpayer compliance, tax knowledge has a significant effect on taxpayer compliance, tax inspection have a significant effect on taxpayer compliance and taxpayer compliance has a significant effect on surface water tax revenues. The results of the mediation test show that tax compliance is able to mediate tax quality, tax knowledge, and tax inspection on surface water tax revenues